Development and validation of a model to predict the need for emergency front‐of‐neck airway procedures in trauma patients. (1st December 2019) - Okada, Y.; Hashimoto, K.; Ishii, W.; Iiduka, R.; Koike, K.
Summary: The present study aimed to develop and validate a model for predicting the need for emergency front‐of neck airway (eFONA) procedures among trauma patients. This was a multicentre retrospective cohort study using data from the Japan Trauma Data Bank between January 2004 and December 2017. Only adult trauma patients were included. The cohort was divided into development and validation cohorts. A simple scoring system was developed to predict the necessity for emergency front‐of neck airway procedures in the development cohort using a logistic regression model. The external validity and diagnostic ability of the scoring system was assessed in the validation cohort. In total, 198, 182 out of 294, 274 patients were included; emergency front‐of‐neck airway occurred in 467 patients (0.24%) they were divided into development (n = 100, 120 with 0.22% undergoing emergency front‐of neck airway) and validation (n = 98, 062 with 0.25% undergoing emergency front‐of neck airway) cohorts. The 'eFONA' prediction scoring system was developed in the development cohort, with a score of +1 for each of the following: E ye opening (no eye opening in response to any stimuli); F all from height or motor bike; O ral–maxillofacial injury; N eck tracheal injury; and A irway management by paramedics. In the validation cohort, the C‐statistic of the scoring system was 0.820. Setting the cut‐off value at one for rule‐out, the sensitivity and negative likelihood ratios were 0.86 and 0.22, respectively. Setting the cut‐off value at two for rule‐in, the specificity and positive likelihood ratios were 0.91 and 6.6, respectively. The present scoring system may assist in predicting the need for emergency front‐of neck airway procedures among the general trauma population.